Efficient adsorption of basic fuchsin dye using thermally engineered novel smart nanocomposites - Ehab A. Abdelrahman (Scientific Reports)
Abstract Basic fuchsin dye is known for its genotoxic, neurotoxic, and carcinogenic effects on humans and its long-term persistence and ecological toxicity in aquatic environments. In this study, novel MgO/BaCO3/BaCrO4/C nanocomposites were fabricated through a Pechini-type sol-gel strategy and thermally treated at 600 and 800 oC to yield MB600 and MB800, respectively, for the effective adsorption of basic fuchsin from water-based solutions. The crystalline phases were identified using X-ray diffraction patterns, indicating the formation of crystalline MgO, BaCO3, and BaCrO4 phases, with average crystallite sizes of 60.70 and 75.64 nm for MB600 and MB800, respectively. Energy dispersive X-ray spectroscopy revealed the atomic composition, with MB600 containing 21.3% C, 51.1% O, 10.2% Mg, 2.8% Cr, and 14.6% Ba, while MB800 showed enhanced metal content and reduced carbon residues. Field emission scanning electron microscope and high-resolution transmission electron microscope micrographs demonstrated morphological evolution with increasing calcination temperature and average particle sizes of 13.7 and 32.1 nm for MB600 and MB800, respectively. MB600 exhibited a maximum adsorption capacity of 442.48 mg/g, outperforming MB800 at 375.94 mg/g. The sorption mechanism was spontaneous, exothermic, physisorption, and best described by the pseudo-first-order model in addition to the Langmuir isotherm, demonstrating monolayer coverage and uniform surface binding.